[Afisz. Incipit] Przegląd filmów polskich 30.X.- 28.XI.1954. (Gdańsk : [wydawca nieznany], 1954)
Afisz informujący o przeglądzie filmów w Elblągu.
Keywords: Elbląg (Polska) -- 1945-1970 -- druki ulotne; Druki ulotne -- 1945-1970.